2012
DOI: 10.1016/j.neuropharm.2011.07.027
|View full text |Cite
|
Sign up to set email alerts
|

Magnesium deficiency induces anxiety and HPA axis dysregulation: Modulation by therapeutic drug treatment

Abstract: Preclinical and some clinical studies suggest a relationship between perturbation in magnesium (Mg2+) homeostasis and pathological anxiety, although the underlying mechanisms remain largely unknown. Since there is evidence that Mg2+ modulates the hypothalamic-pituitary adrenal (HPA) axis, we tested whether enhanced anxiety-like behaviour can be reliably elicited by dietary Mg2+ deficiency and whether Mg2+ deficiency is associated with altered HPA axis function. Compared with controls, Mg2+ deficient mice did i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
98
2
8

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(111 citation statements)
references
References 75 publications
(66 reference statements)
3
98
2
8
Order By: Relevance
“…При дефиците Mg 2+ как явном, так и субкомпенсированном проницаемость клеточной мембраны для ионов Na + и Ca 2+ стано-вится патологически усиленной, что приводит: 1) к гипервозбудимости ГГНО, 2) увеличению транскрипции кортикотропин-рилизинг-фактора в паравентрикулярном ядре гипоталамуса, 3) повышению адренокортикотропного гормона плазмы [14,16,17].…”
Section: этап 2 выбор оптимальной тактики и длительности лечения стрunclassified
See 1 more Smart Citation
“…При дефиците Mg 2+ как явном, так и субкомпенсированном проницаемость клеточной мембраны для ионов Na + и Ca 2+ стано-вится патологически усиленной, что приводит: 1) к гипервозбудимости ГГНО, 2) увеличению транскрипции кортикотропин-рилизинг-фактора в паравентрикулярном ядре гипоталамуса, 3) повышению адренокортикотропного гормона плазмы [14,16,17].…”
Section: этап 2 выбор оптимальной тактики и длительности лечения стрunclassified
“…Данные современных зарубежных и российских исследований свидетельствуют о негативном влиянии как дефи-цита магния, так и низкого его содержания в организме [17,33]. Низкое содержание магния в пище приводит к повреждению белков головного мозга и биохимических путей, содействуя диз-регуляции при аффективных расстройствах [34].…”
Section: этап 3 выбор оптимальной профилактики стрессаunclassified
“…Numerous studies have shown that nutritional deficits during fetal and early postnatal development adversely impact upon neural development and behaviour, and dietary Mg deficiency during adulthood exacerbates anxiety-and depressive-like behaviours [19,20] However, there is limited information regarding the potential impact of Mg deficiency during the crucial developmental period, and the potential impact gestational Mg deficiency on adult offspring. In this study, we used a model of moderate maternal Mg deficiency [5] to evaluate the effects of gestational Mg deficiency on hippocampal NMDAR expression and behaviour in offspring.…”
Section: Introductionmentioning
confidence: 99%
“…Appetite dysregulation and Type 3 diabetes have been linked to higher brain dysregulations (higher cerebral cortex areas) that corrupt the hypothalamus, sympathetic and non-sympathetic nervous system with close connections between magnesium and Sirt1 in the regulation of the circadian rhythm [4] [33], stroke [34]- [37], NAFLD [38]- [40] diabetes [41]- [47] and neurodegenerative diseases [48]- [52].…”
Section: Introductionmentioning
confidence: 99%